2018
DOI: 10.2147/cmar.s146658
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant treatments in triple-negative breast cancer patients: where we are now and where we are going

Abstract: Triple-negative breast cancer (TNBC) remains the poorest-prognosis breast cancer (BC) subtype. Gene expression profiling has identified at least six different triple-negative subtypes with different biology and sensitivity to therapies. The heterogeneous nature of TN tumors may justify the difficulty in treating this BC subtype. Several targeted agents have been investigated in clinical trials without demonstrating a clear survival benefit. Therefore, systemic chemotherapy remains the cornerstone of current cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 129 publications
(147 reference statements)
1
57
0
2
Order By: Relevance
“…TNBC is an aggressive malignancy and is prone to recurrence and metastasis . In this study, we found that EDNRB silencing caused the differential expression of 248 proteins, and these proteins belong to different functional categories that are found in cellular organelles and are involved in BPs such as signal transduction.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…TNBC is an aggressive malignancy and is prone to recurrence and metastasis . In this study, we found that EDNRB silencing caused the differential expression of 248 proteins, and these proteins belong to different functional categories that are found in cellular organelles and are involved in BPs such as signal transduction.…”
Section: Discussionmentioning
confidence: 77%
“…Therapeutic approaches such as surgical resection, hormone therapies, target‐specific immunotherapies, radiotherapies, and chemotherapies, together with regular screening and early diagnosis, have significantly improved the survival of most breast cancer patients . However, tumor recurrence, metastasis, and drug resistance are still threats for patients with breast cancer, particularly for those with basal‐like triple‐negative breast cancer (TNBC) because TNBC is insensitive to most available therapies . Currently, the pathogenesis of TNBC is incompletely understood and there is little information on reliable therapeutic targets for treatment of TNBC in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…The second advantage is that NACT can eradicate tumor cells from axillary lymph nodes, which helps downstage the cancer and avoid the morbid procedure of axillary lymph node dissection. The third benefit is that it provides an important in vivo observation of the chemosensitivity of the tumor (21).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is a common malignant tumor in women and its incidence increases every year; it has therefore become a serious threat to women's health (1,2). In recent years, there has been marked progress in the diagnosis and treatment of breast cancer; however, patient mortality has not been significantly improved (3,4). Currently, Triple Negative Breast Cancer (TNBC) with all negative estrogen receptor/progesterone receptor/human epidermal growth factor receptor-2 has become a growing concern for clinicians (5).…”
Section: Introductionmentioning
confidence: 99%